Utilization of Biogas Waste (Sludge) as an Alternative to Fish Feed in Teluk Roban Sorkam Village, Central Tapanuli Regency - Fiki Harjuni; Mhd Aidil Huda; Husnul Yaqin Harahap; Farhan Ramdhani; Lauura Hermala Yunita; Muhammad Latiful Khobir; Mutiara Al-Khayakni; Herman Sarumaha; Shofian Nanda Adiprayoga; Rahayu Ningsih Hutabarat (LPPM Universitas Muhammadiyah Tasikmalaya, 2022)
Fish feed is one of the highest cost components in carrying out intensive system fish farming activities which makes the high price of feed will affect the continuity of the aquaculture business. For fish cultivators, high feed prices will cause difficulties because about 60% of production costs come from feed. The high cost of feed is partly due to the fact that some of the raw materials for feed are still imported. Biogas waste from cow dung is a potential source of alternative raw material for fish feed with adequate quality of carbohydrate nutrients accompanied by guaranteed quantities and availability throughout the year. The purpose of this activity is to socialize in the manufacture of fish feed from biogas waste from cow dung in Teluk Roban Village, Sorkam Tapanuli Tenah District. The method used is to carry out direct training activities with demonstrations of the procedures and stages of making fish feed in the form of pellets for fish cultivators and the community. The results obtained from this activity are expected to be later for fish cultivators or community groups to understand the manufacture of fish feed in the form of pellets from biogas waste from cow dung as a business that can fill the local market that has not been filled with much and can compete in the business of making fish feed. . With this activity, it is hoped that there will be an increase in the skills of making fish feed in the form of commercial-scale pellets for the local market